TENDÊNCIAS IDEOLÓGICAS E FUNÇÃO SOCIAL DA EDUCAÇÃO EM MUSEUS DO ESTADO DE SÃO PAULO - BELTRAME, RENAN RIBEIRO (2018)
This research seeks to consider in a historical context, the ideological tendencies perpetrated by educational practices implemented in history museums in the State of São Paulo. At first, we established a context of the development of the museum institutions in the State, and later we analyze the content of interviews with professionals and visitors of two state museums. Using a theoretical basis based on the concepts and analyzes of Louis Althusser, this study seeks to identify the agents, mechanisms and ideological inculcation contents constituted first in the context in which the museums, understood as Cultural Ideological State Apparatus, are managed directly by the State Bureaucratic Apparatus and then by the Social Organization (SO) System. This study to identify that in the both contexts, the social function played by education in history museums belonging to the Government of the State of São Paulo is to serve as a means of promoting a dominant ideological tendency.